Unlimited love : altruism, compassion, and service - Post, Stephen G. (Stephen Garrard), 1951- (Templeton Foundation Press, 2003)
What if we could prove that love heals mental illness and is vital to successful therapeutic outcomes in all areas of health care? What if we could prove that people who live more for others than for self have greater psychological well-being?In Unlimited Love, Post examines the question of what we mean by ""unlimited love""; his focus is not on ""falling"" into love, which is ""altogether natural, easy, and delusional."" Rather, he focuses on the difficult learned ascent that ""begins with insight into the need for tolerance of ubiquitous imperfection, and matures in.